Návrh regulace tahu komína - Toman, Marek (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2013)
Tato práce se zabývá řešením problematiky nadměrného tahu komína. V úvodní části práce jsou shrnuty možnosti regulace tahu komína. Následně je sestaven matematický model tahu komína, který názorně popisuje chování komína jako dynamické soustavy. Poté je popsána výroba jednoduché řídící jednotky určené k regulaci tahu komína. Hlavním cílem práce je návrh a výroba řídící elektroniky založené na mikrokontroléru dsPIC.

This paper talks about problematics of excessive chimney draft. In the first part of the thesis the possibilities of chimney draft adjustability are summarized. Subsequently, a mathematical model, which describes the behavior of the chimney as a dynamic system, is built. Then a simple production control unit development is described. This control unit si designed to control the chimney draft. The main goal of this work is to design and manufacture electronic control based on the dsPIC microcontroller.
Design of Chimney Effect Control
Keywords: Tah komína; teplotní čidlo; displej; regulace; servomotor; Chimney effect; temperature sensor; display device; control; servo-engine